Toward an Integrated and Differential Approach to the Relationships Between Loneliness, Different Types of Facebook Use, and Adolescents’ Depressed Mood - Frison, Eline and Eggermont, Steven (Communication Research, 2020)
Although a variety of studies have examined the predictors or outcomes of adolescents’ social networking site use, these studies did not incorporate (1) an integrated, longitudinal approach to examine these relationships longitudinally in a single comprehensive model or (2) a differential approach to distinguish between different types of social networking site use. Therefore, this two-wave panel study ( N = 1,612) developed an integrated and differential model to provide a deeper understanding of the relationships among loneliness, specific types of Facebook use, and adolescents’ depressed mood. Using structural equation modeling, the results point to the presence of a poor-get-richer effect regarding active public Facebook use but reveal a poor-get-poorer effect regarding passive Facebook use. The discussion focuses on the explanation and understanding of these findings.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjE1NjE3NTA2